Aesthetic Expressions in Ḍeuḍā Song Lyrics: An Analysis of Shreeṅgār and Karuṇa Rasas - Air, Narendra Bahadur (The Batuk, 2025)
In recent years, many authors have shed light on the hidden world of folklore, particularly on folk songs seeking to re-envision the practices of the traditional society. This research on a folk song of Far Western Nepal i.e. Ḍeuḍā holds special promise for analyzing it in the light of Rasa theory; a theory about aesthetic flavor in arts that evokes emotions and feelings of the readers. The study reflects upon the theory of rasa and attempts to make an assessment of it in relation to the Deudā song that adopts qualitative research method, using observations and interviews as data collections tools. The main intention of this study is to see how the song lets out the common emotions (rasas) of the people dwelling in Far Western Nepal. It examines how different forms of rasa function in various Deudā songs. A particular emphasis is placed on analyzing the songs in terms of Shreeṅgār and Karuṇa rasas. The findings of the study reveal that the Deudā song is loaded with the feeling of the throbbing hearts of the people of the region with their emotions of pain, pathos, suffering, misery, hardships, compassion, mercy, love and romance.